Internal herniation of the caecum and the ascending colon through the foramen of Winslow. Issue 3 (2nd March 2020) - Azer, Mina; Lira-Schuldes, Alejandro-Daniel; Volkers, Hans-Uwe
Abstract: We are reporting a case of internal herniation of the bowel through the foramen of Winslow. This is a very rare condition that prompts an urgent operative intervention due to its potential fatal complications, as it is usually accompanied by bowel strangulation and ischemia. Due to the vague clinical picture, the diagnosis only reached using imaging techniques such as computed tomography or as a surgical surprise during the operation. Key aspects of surgical interventions are hernia reduction, bowel resection in case of non-viable ischemic bowel and the highly debatable recurrence prevention maneouvres.